An Autotaxin/Lysophosphatidic Acid/Interleukin‐6 Amplification Loop Drives Scleroderma Fibrosis - Castelino, Flavia V.; Bain, Gretchen; Pace, Veronica A.; Black, Katharine E.; George, Leaya; Probst, Clemens K.; Goulet, Lance; Lafyatis, Robert; Tager, Andrew M. (Arthritis & rheumatology (Hoboken, N.J.), 2016)
Objective We previously implicated the lipid mediator lysophosphatidic acid (LPA) as having a role in dermal fibrosis in systemic sclerosis (SSc). The aim of this study was to identify the role of the LPA‐producing enzyme autotaxin (ATX), and to connect the ATX/LPA and interleukin‐6 (IL‐6) pathways in SSc. Methods We evaluated the effect of a novel ATX inhibitor, PAT‐048, on fibrosis and IL‐6 expression in the mouse model of bleomycin‐induced dermal fibrosis. We used dermal fibroblasts from SSc patients and control subjects to evaluate LPA‐induced expression of IL‐6, and IL‐6–induced expression of ATX. We next evaluated whether LPA‐induced ATX expression is dependent on IL‐6, and whether baseline IL‐6 expression in fibroblasts from SSc patients is dependent on ATX. Finally, we compared ATX and IL‐6 expression in the skin of patients with SSc and healthy control subjects. Results PAT‐048 markedly attenuated bleomycin‐induced dermal fibrosis when treatment was initiated before or after the development of fibrosis. LPA stimulated expression of IL‐6 in human dermal fibroblasts, and IL‐6 stimulated fibroblast expression of ATX, connecting the ATX/LPA and IL‐6 pathways in an amplification loop. IL‐6 knockdown abrogated LPA‐induced ATX expression in fibroblasts, and ATX inhibition attenuated IL‐6 expression in fibroblasts and the skin of bleomycin‐challenged mice. Expression of both ATX and IL‐6 was increased in SSc skin, and LPA‐induced IL‐6 levels and IL‐6–induced ATX levels were increased in fibroblasts from SSc patients compared with controls. Conclusion ATX is required for the development and maintenance of dermal fibrosis in a mouse model of bleomycin‐induced SSc and enables 2 major mediators of SSc fibrogenesis, LPA and IL‐6, to amplify the production of each other. Our results suggest that concurrent inhibition of these 2 pathways may be an effective therapeutic strategy for dermal fibrosis in SSc.